Rock vs cocktails Molotov : la violence politique pendant les concerts dans l’Italie de la fin des années 1970 - Céline Pruvost (Criminocorpus)
In Italy at the end of the seventies, many artists are questioned on stage, in violent forms which range from invective to political trial, including shooting, throwing stones or even Molotov cocktails. We herein propose a study of rock facing this political violence context: when there is violence from part of the public towards the artists, what is the impact on concerts and on works? After presenting the Italian context features, we describe the violence which affected international rock stars during their concerts in Italy. We then show how this political violence had an unexpected practical and esthetic consequences, far beyond rock, strongly impacting the field of Italian song.